Epitaxial GaInP/GaAs/Si Triple‐Junction Solar Cell with 25.9% AM1.5g Efficiency Enabled by Transparent Metamorphic AlxGa1−xAsyP1−y Step‐Graded Buffer Structures. Issue 5 (14th March 2021) - Feifel, Markus; Lackner, David; Schön, Jonas; Ohlmann, Jens; Benick, Jan; Siefer, Gerald; Predan, Felix; Hermle, Martin; Dimroth, Frank
Abstract : III–V/Si multi‐junction solar cells are potential successors to the silicon single‐junction cell due to their efficiency potential of up to 40% in the radiative limit. [1] Herein, latest results of epitaxially integrated GaInP/GaAs/Si triple‐junction cells are presented. To reduce parasitic absorption losses, which have limited the current density in the Si bottom cell in the previous devices, transparent Al x Ga1– x As y P1– y step‐graded metamorphic buffers are investigated. Compared with previous GaAs y P1– y step‐graded buffers, the transmittance is enhanced significantly, while no significant impact on the threading dislocation density is observed. Implemented into a new triple‐junction solar cell, an increase in short‐circuit current density from 10.0 to 12.2 mA cm − 2 is achieved, leading to a new record conversion efficiency of 25.9% under AM1.5g conditions. Abstract : Herein, latest results of epitaxially integrated GaInP/GaAs/Si triple‐junction cells are presented. Through the development of transparent Al x Ga1– x As y P1– y step‐graded metamorphic buffers, parasitic absorption is successfully avoided and the current density is increased from 10.0 to 12.2 mA cm − 2 . The final device achieves a new record AM1.5g conversion efficiency of 25.9%.